PENGARUH JENIS ZAT PENGATUR TUMBUH ALAMI DAN LAMA PERENDAMAN TERHADAP PERTUMBUHAN STEK TANAMAN LADA (Piper nigrum L.) - Mutia, Sri; Syukri, Syukri; Marnita, Yenni (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This research aims to determine the effect of the type of natural growth regulator and the length of soaking on the growth of pepper plant cuttings. The experimental design used was a factorial randomized block design consisting of 2 factors. Factor I is the influence of giving several types of natural ZPT and factor II is the length of soaking. The results of the research concluded that the type of natural growth regulator had a very significant effect on the growth percentage of pepper cuttings and shoot height, but had no significant effect on the number of shoots, number of leaves, root length and root weight. The treatment of onion extract and coconut water provided the best growth of pepper cuttings. The length of soaking had a very significant effect on the growth percentage of pepper cuttings and shoot height, but had an insignificant effect on the number of shoots, number of leaves, root length and root weight. Soaking time of 20 minutes provides the best growth of pepper cuttings. The interaction between the type of natural growth regulator and the length of soaking had a very significant effect on growth percentage and shoot height, but had no significant effect on shoot height, number of shoots, number of leaves, root length and root weight. The best interaction on the percentage of growth of pepper cuttings was the Z0L3, Z1L1, Z1L2, Z1L3, Z2L1, Z2L2 treatment, while the shoot height and age were the Z2L3 combination.